2019
DOI: 10.1186/s12864-019-5947-z
|View full text |Cite|
|
Sign up to set email alerts
|

Small RNA discovery in the interaction between barley and the powdery mildew pathogen

Abstract: Background Plants encounter pathogenic and non-pathogenic microorganisms on a nearly constant basis. Small RNAs such as siRNAs and miRNAs/milRNAs influence pathogen virulence and host defense responses. We exploited the biotrophic interaction between the powdery mildew fungus, Blumeria graminis f. sp. hordei ( Bgh ), and its diploid host plant, barley ( Hordeum vulgare ) to explore fungal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 125 publications
2
37
0
Order By: Relevance
“…Following the publication of the original article [1], the authors noted several typesetting errors which are noted in this Correction article.…”
mentioning
confidence: 99%
“…Following the publication of the original article [1], the authors noted several typesetting errors which are noted in this Correction article.…”
mentioning
confidence: 99%
“…The reason may be that the collected P. italicum samples were not at different developmental stages or at the infectious stage in the citrus fruit. It has been reported that Pt-sRNA can be especially accumulated in Penicillium triticina-infected wheat leaf tissue [48] and that a number of Blumeria graminis sRNAs were significantly differentially expressed at 0 to 48 h after inoculation in barley [18]. These findings reflect that internal needs or environmental stresses might form a feedback regulation mechanism to stimulate the accumulation of sRNAs in fungi or oomycetes.…”
Section: Discussionmentioning
confidence: 78%
“…The role of miRNAs in the PM response has been reported in wheat (Xin et al, 2010;Wu et al, 2015) and barely (Hunt et al, 2019), but the relationship between miRNAs and cucumber PM resistance is still not clear. The scanning electron microscopy results showed a higher density of PM hyphae on the leaf surface of D8 than on SSSL508-28 48 h after inoculation (Figure 1), which reflected their different responses to PM.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, miRNAs related to the response of barley to PM (B. graminis f. sp. hordei) were putatively identified as regulating the transcript levels of transcription factors (TFs), such as auxin response factors, NAC [for NAM (no apical meristem), ATAF, CUC (cup-shaped cotyledon)], and homeodomains, as well as several splicing factors (Hunt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%